2008
DOI: 10.1213/ane.0b013e318173251f
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adenosine A2A Receptors in the Rat Lumbar Spinal Cord and Implications in the Modulation of N-Methyl-d-Aspartate Receptor Currents

Abstract: BACKGROUND: The presence of A 2A receptors in the dorsal horn of the spinal cord remains controversial. At this level, activation of N-methyl-d-aspartate (NMDA) receptors induces wind-up, which is clinically expressed as hyperalgesia. Inhibition of NMDA receptor currents after activation of A 2A receptors has been shown in rat neostriatal neurons. In this study, we sought to establish the presence of adenosine A 2A receptors in the lamina II of the rat lumbar dorsal horn neurons and investigated whether the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Thus, A 2A R are selective controllers of adaptive changes of synaptic efficiency. This is in accordance with the ability of A 2A R to enhance the evoked release of glutamate in different brain areas (Lopes et al 2002;Marchi et al 2002;Rodrigues et al 2005;Ciruela et al 2006a;Shen et al 2013;Matsumoto et al 2014;Machado et al 2016) and the function of ionotropic glutamate receptors (Wirkner et al 2004;Guntz et al 2008;Rebola et al 2008;Azdad et al 2009;Higley and Sabatini 2010;Dias et al 2012;Scianni et al 2013;Di Angelantonio et al 2015;Sarantis et al 2015). A 2A R also act as fine-tuners of other neuromodulation systems (Ribeiro 1999;Ribeiro 2000, 2009), since A 2A R activation is required to observe synaptic effects of growth factors (Di ogenes et al 2004;Flajolet et al 2008;Gomes et al 2009) or neuropeptides (Sebastião et al 2000a;Cunha-Reis et al 2007).…”
Section: Role Of Adenosine Receptors In the Brainsupporting
confidence: 54%
“…Thus, A 2A R are selective controllers of adaptive changes of synaptic efficiency. This is in accordance with the ability of A 2A R to enhance the evoked release of glutamate in different brain areas (Lopes et al 2002;Marchi et al 2002;Rodrigues et al 2005;Ciruela et al 2006a;Shen et al 2013;Matsumoto et al 2014;Machado et al 2016) and the function of ionotropic glutamate receptors (Wirkner et al 2004;Guntz et al 2008;Rebola et al 2008;Azdad et al 2009;Higley and Sabatini 2010;Dias et al 2012;Scianni et al 2013;Di Angelantonio et al 2015;Sarantis et al 2015). A 2A R also act as fine-tuners of other neuromodulation systems (Ribeiro 1999;Ribeiro 2000, 2009), since A 2A R activation is required to observe synaptic effects of growth factors (Di ogenes et al 2004;Flajolet et al 2008;Gomes et al 2009) or neuropeptides (Sebastião et al 2000a;Cunha-Reis et al 2007).…”
Section: Role Of Adenosine Receptors In the Brainsupporting
confidence: 54%
“…In addition to these behavioural changes, we found a large reduction in the level of Conflicting results have been obtained from binding studies and autoradiography [3,7,8], and functional studies have reported some inconsistent effects of A 2A receptor ligands [1,5,15,16,25,28,36]. mRNA for the A 2A receptor has been reported to be expressed in the dorsal root ganglion but not in the spinal cord [20,21] suggesting that A 2A receptors could be present on the peripheral terminals of the sensory nerves but not to any significant extent in the spinal cord, as suggested by Sawynok [32].…”
Section: Introductionsupporting
confidence: 45%
“…More recent studies have however detected mRNA for the A 2A receptor in rat and mouse spinal cord [6,16], and it has been suggested that these may on be on …”
Section: Introductionmentioning
confidence: 99%
“…A2ARs are found on both glial cells (Gyoneva et al, 2009) and neurons (Guntz et al, 2008) and activation following inflammation has been shown to increase IL-10 and decrease proinflammatory molecules released from a variety of different inflammatory cell types in culture (Grinberg et al, 2009; Hasko et al, 1996; Khoa et al, 2001; Link et al, 2000; Perez-Aso et al, 2013; Vincenzi et al, 2013a, 2013b). Interestingly, the A2AR is upregulated on macrophages and microglia following inflammatory signals such as LPS, CpG, lipoteichoic acid, or TNF, and on lymphocytes from MS and ALS patients, providing a unique pharmacological target for immune cells and glia exclusively activated by prior proinflammatory signals (Grinberg et al, 2009; Gyoneva et al, 2009; Vincenzi et al, 2013a, 2013b).…”
Section: Therapeutic Potential Of Il-10-based Therapies: Setting Tmentioning
confidence: 99%